THE INFLUENCE OF PARENTS’ ACTIVE PARTICIPATION AND LEARNING DISCIPLINE TOWARDS STUDENTS ENGLISH LEARNING ACHIEVEMENT - Ida Wachyuningsih; Syahfitri Purnama (Universitas Indraprasta PGRI, 2018)
The purposes of this research are to find out the simultaneously influences of parents’ active participation and learning discipline towards students English learning achievement, to find out the influence of parents’ active participation towards students English learning achievement and to find out the influence of learning discipline towards students English learning achievement. The reseach method that used is survey. The samples are 87 students who chosen randomly from all students of VII level of MTS Negeri at Cipayung Sub – Distric, East Jakarta. The data collection are carried out by distributing quisioner. The data analysis use descriptive method, pearson multiple correlation coefficient, determination coefficient, regression analysis. The statistic test is used Fcount and Tcount. This research is implemented on April 30 th till Mei 18th 2018. The results of this research draw: (1) Parents’ active participation and learning discipline simultaneously have positive and relevant influences towards students English learning achievement with multiple correlation coefficient r = 0,524. Parents’ active participation and learning discipline simutaneosly distribute 27,4% towards students English learning achievement through significant multiple regression equation = -13,777 + 0,471 X1 + 0,360 X2 with sig score 0,000 < 0,05 dan Fcount = 20.879 ; (2) Parents’ active participation has a relevant influence towards students English learning achievement. It is proven by getting sig score 0,000 < 0,05 and tcount = 4,525; (3) Learning disciple has a significat influence towards students English learning achievement. It si proven by getting score Sig. 0,000 < 0,05 dan tcount = 3,449 Key words : Parents’ active participation, Learning discipline, Learning achievement